Pertanggungjawaban Pidana Bandar Judi Online Dalam Politik Hukum Pidana Di Indonesia - Rahman; Agung Pamungkas; Syawal; M. Syahlan Samosir (University Of Bengkulu Law Journal, 2026)
As a result of technological advances, cyber crime is on the rise, such as the widespread, coordinated, and multinational expansion of online gambling. In practice, online bookies play a role as system controllers, facility providers, and the primary beneficiaries of gambling activities. In terms of Indonesian criminal law policy, this study seeks to assess the trajectory of criminal liability policy for online gambling site operators and to trace the trajectory of criminal law policy since the enactment of the National Criminal Code. Normative legal research utilizing conceptual methods, statutory law, and criminal law policy is the study technique used. The study findings show that the regulation of criminal liability for online bookies remains scattered across various legal instruments, from the Criminal Code, the Electronic Information and Transactions Law (ITE), to Undang-Undang No 1 of 2023 concerning the Criminal Code. The current direction of criminal law policy in Indonesia tends to prioritize a repressive approach through criminalization and law enforcement, but is gradually shifting toward a more integrative approach combining preventive, repressive, and rehabilitative aspects. To achieve legal clarity and true justice in criminal prosecution of online gambling bookies, a more modern and flexible approach to criminal law policy-making is needed.